Pemanfaatan Tumbuhan Air Menjadi Pupuk Organik Cair dengan Teknik Fermentasi di Kampung Yoboi Sentani Papua - Ika Widiastuti; Rusman Latief (Perkumpulan Dosen Program Hibah Indonesia (PDPHI), 2024)
Hydrilla verticillata, Pistia stratiotes (Apu-apu), and Eichhornia crassipes (Water hyacinth) are aquatic plants that grow abundantly in the waters of Yoboi Village, Lake Sentani. Currently, these aquatic plants have become weeds and are causing water transportation problems between villages. The aim of this service is to train the people of Yoboi Village to utilize the aquatic plants Hydrilla verticillata, Pistia stratiotes (Apu-apu), and Eichhornia crassipes (Water hyacinth) into liquid organic fertilizer (POC) using fermentation techniques with EM-4. The target of training activities is caregiver mothers. Training activities were carried out in two meetings. Based on the pre-test results, 80% of the mothers did not understand the benefits of fertilizer and did not understand how to make POC. The methods used are lectures, discussions and practice. The result of the training is that the caregivers understand and understand how to make POC from aquatic plant materials using the EM-4 fermentation technique. Through this service activity, the Yoboi Village community has changed the paradigm regarding Hydrilla verticillata, Pistia stratiotes, and Eichhornia crassipes, which are weeds and become useful plants